Crisis management during anaesthesia: desaturation. Issue 3 (2nd June 2005) - Szekely, S M; Runciman, W B; Webb, R K; Ludbrook, G L
Abstract : Background: Desaturation occurs for many reasons under anaesthesia, some rare and obscure, and many potentially life threatening. The rapidity with which the cause is determined and appropriate management is instituted varies considerably between anaesthetists. Objectives: To examine the role of a previously described "core" algorithm COVER ABCD–A SWIFT CHECK, supplemented by a specific sub-algorithm for desaturation, in the management of incidents of desaturation occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: Amongst the first 4000 incidents reported to AIMS there were 584 episodes of desaturation in association with general anaesthesia; 41% were dealt with by COVER, 48% by ABCD, and 11% required a specific desaturation sub-algorithm. Nearly a fifth of all desaturations were caused by endobronchial intubation. Within the specific desaturation subgroup, half were due to pulmonary problems in the form of underlying lung disease, excessive secretions or obesity and a third could not be diagnosed. Conclusion: Desaturation may have many causes, some of which are obscure, and failure to respond promptly may place the patient at risk. In the face of persistent desaturation, management should consist of hand ventilation with 100% oxygen, completion of COVER ABCD–A SWIFT CHECK, and a return to a supine posture. Blood gases, chest radiography, and bronchoscopy may be required where desaturation is persistent and/or no apparent causes can be found.